2021
DOI: 10.1111/jon.12941
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic network is related to surgical outcome in temporal lobe epilepsy with hippocampal sclerosis: A brain FDG‐PET study

Abstract: Background and Purpose The aim of this study was to investigate differences in metabolic networks based on preoperative fluorodeoxyglucose (FDG)‐positron emission tomography (PET) in temporal lobe epilepsy (TLE) with hippocampal sclerosis (HS) between patients with complete seizure‐free (SF) and those with noncomplete seizure‐free (non‐SF) after anterior temporal lobectomy. Methods This study was retrospectively performed at a tertiary hospital. We recruited pathologically confirmed 75 TLE patients with HS who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…One of the major findings of the present study is the increased connectivity within the operated temporal lobe observed in the > IA groups compared to the IA groups in both left and right TLE (clusters of 7.5 vs 3.3 cm 3 and 2.6 cm 3 vs 2.2 cm 3 for left and right TLE respectively, Table 3 ). This is consistent with recent metabolic connectivity studies based on graphical analyses, gathering left-lateralized and right-lateralized patients, that reported higher functional connectivity in patients who were not seizure-free ( Cho et al, 2022 , Ren et al, 2021 , Yu et al, 2018 ). The main hypothesis is that the persistent seizure group has over-excitatory brain activity compared to seizure-free patients as indicated by strengthened brain connections, allowing seizures to occur and to propagate more readily.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…One of the major findings of the present study is the increased connectivity within the operated temporal lobe observed in the > IA groups compared to the IA groups in both left and right TLE (clusters of 7.5 vs 3.3 cm 3 and 2.6 cm 3 vs 2.2 cm 3 for left and right TLE respectively, Table 3 ). This is consistent with recent metabolic connectivity studies based on graphical analyses, gathering left-lateralized and right-lateralized patients, that reported higher functional connectivity in patients who were not seizure-free ( Cho et al, 2022 , Ren et al, 2021 , Yu et al, 2018 ). The main hypothesis is that the persistent seizure group has over-excitatory brain activity compared to seizure-free patients as indicated by strengthened brain connections, allowing seizures to occur and to propagate more readily.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, even after anterior temporal lobectomy and removal of the epileptogenic zone, the epileptogenic network may persist in patients with increased connectivity with these network differences contributing to the surgical outcomes of TLE patients. Indeed, Cho et al observed a more increased assortative coefficient in non-seizure-free patients, implicating that the epileptogenic network is more robust to removal of the epileptogenic zone ( Cho et al, 2022 ). In our study, these findings cannot be explained by the longer duration of disease observed in IA patients compared to > IA patients since it may have led to stronger connections in IA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 Some studies have assessed the association between surgical outcomes and MRI markers in TLE with HS. 29 30 31 One of the purposes of our study was to determine the potential clinical significance of MB atrophy in predicting surgical outcomes. Surgical outcomes following anterior temporal lobectomy were good in 58% of patients in the present study, which was similar to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used modality to determine functional connectivity is rs-fMRI;(6, 7) however, there are also other various methods, including electroencephalography (EEG), (10) magnetic encephalography (MEG), (11) and positron emission tomography (PET), to investigate functional connectivity. (12) One modality recently used to determine functional connectivity is functional nearinfrared spectroscopy (fNIRS). ( 13) fNIRS is an optical technique that uses near-infrared spectroscopy to monitor the brain.…”
Section: Introductionmentioning
confidence: 99%